Práticas e saberes da professora pomerana : um estudo sobre interculturalidade - Dettmann, Jandira Marquardt (2014)
This research analyses practices and knowledge of a Pomeranian teacher in a countryside elementary school in Santa Maria de Jetibá, in the state of Espírito Santo, in Brazil, aiming at problematizing culture and intercultural issues. Reflections on which contributions these practices have given to an intercultural school education have been deepened. It benefits from a case study to analyze documents, classes observations, participant observations during planning, semi structured interviews with the teacher, and field notes. Issues on the history of Pomeranian descendants as well as on the main academic productions that refer to this traditional people education have been considered. Theoretical and methodological discussions contribute to the understanding and foundation of some key concepts, such as: cultures(s) (THOMPSON, 1995; GEERTZ, 2012), interculturalism (CANDAU, 2005; FORNET-BETANCOURT, 2004), school culture, culture of school (FORQUIN, 1993), teachers practices (FREIRE, 1996), teachers knowledge (TARDIF, 2012), partnerships (FOERSTE, 2005) etc. It points out that the Pomeranian teacher’s practices were part of the school context before PROEPO (Pomeranian School Education Program) was launched concerning the oral usage of the Pomeranian language within the classroom. The teacher’s practices were reframed within interaction with cultural knowledge, experiences, and collectivities produced on both community and school dynamics. These practices allow the dialog between school culture and the culture of the school, by promoting the experiences of local knowhow and the access to the universal knowledge. One can allege that within the investigated school context there are some conditions that favor the intercultural dimension of pedagogical processes. It is appropriate to deepen the studies on the school education contributions to the bilingual teaching and its impacts to value the Pomeranian culture, and to, eventually, keep this traditional people’s language. Tensions and conflicts were identified on the PROEPO’s approach to the development of reading and writing abilities in Pomeranian language.